2020
DOI: 10.3846/bme.2020.10292
|View full text |Cite
|
Sign up to set email alerts
|

Does Tax Amnesty Influence Intention to Comply?: If Students Are Taxpayers Already

Abstract: Purpose – The implementation of the tax amnesty program in Indonesia is expected to increase the intention to comply. However, the effectiveness of the program is likely to depend on the intention of taxpayer compliance. The purpose of this study is to examine differences in the intention of taxpayer compliance based on perceived justice and the taxpayer’s attitude of the government. Research methodology – Primary data was obtained through experimental research involving 117 students who were enrolled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 23 publications
2
9
0
Order By: Relevance
“…Sometimes a second chance should be given as non-compliance sometimes occurs unintentionally. The finding is consistent with previous studies, which found that tax authority's encouragement through tax amnesty programs could influence tax compliance behaviour (Richardson & Sawyer 2001;Feld et al2006;Saracoglu & Caskurlu 2011;Ahmad Nurkhin et al 2018;Nadiah & Mohammad 2018;Damayanti et al 2020). For the record, SVDP successfully collected additional tax and penalties amounted to RM7.877 billion, with a total of 286,428 taxpayers voluntarily disclosed.…”
Section: Multiple Regression Analysissupporting
confidence: 89%
See 1 more Smart Citation
“…Sometimes a second chance should be given as non-compliance sometimes occurs unintentionally. The finding is consistent with previous studies, which found that tax authority's encouragement through tax amnesty programs could influence tax compliance behaviour (Richardson & Sawyer 2001;Feld et al2006;Saracoglu & Caskurlu 2011;Ahmad Nurkhin et al 2018;Nadiah & Mohammad 2018;Damayanti et al 2020). For the record, SVDP successfully collected additional tax and penalties amounted to RM7.877 billion, with a total of 286,428 taxpayers voluntarily disclosed.…”
Section: Multiple Regression Analysissupporting
confidence: 89%
“…Sometimes a second chance should be given, especially for non-compliance that occurs unintentionally. Previous studies found that encouragement given by tax authorities through tax amnesty programs could influence tax compliance behaviour (Richardson & Sawyer 2001;Feld et al2006;Saracoglu & Caskurlu 2011;Ahmad Nurkhin et al 2018;Nadiah & Mohammad 2018;Damayanti et al 2020). Lastly, our fourth hypothesis is: H4 SVDP by IRBM is positively related to tax compliance among individual taxpayer in Malaysia.…”
Section: H3mentioning
confidence: 70%
“…State income heavily relies on taxes as a crucial source of revenue. (Francis, 2019) Notification Letter (SPT) Notification Letter (SPT) is a letter used by Taxpayers to report the calculation and or payment of taxes, tax objects and or non-tax objects and or assets and obligations in accordance with the provisions of tax laws and regulations (Kevin Lintang, 2017) (Damayanti, Woro, Nastiti, & Supramono, 2020) Taxable Entrepreneur (PKP) (Mardiasmo, 2018) in (Anzeli Maria, 2018) explains that an entrepreneur is an individual or entity in any form which in its business activities or work produces goods, imports goods, exports goods, conducts a trading business, utilizes…”
Section: Taxmentioning
confidence: 99%
“…In line with this matter, also show that perceived fairness of governments' tax systems increases tax compliance. On the contrary, taxpayers who perceive tax systems unfair tend not to comply with tax regulations or not to trust their governments (Damayanti, Nastiti, & Supramono, 2020;Rudolph, 2009). In a similar vein, the formal sector will increase its tax compliance when the formal sector perceives the fairness of tax systems.…”
Section: The Effect Of Tax Fairness On Tax Compliancementioning
confidence: 99%